PRIvacy management responsibility on a scrutinized environment (PRIMROSE): A management method to address privacy challenges - Costa, N.; Duarte de Almeida, I.; Boas da Silva, J. M.; Möhring, M. (EurOMA 2019 Conference Proceedings, 2019)
This paper's theoretical contribution is in reporting an innovative privacy management method designated as PRIMROSE-PRIvacy Management Responsibility On a Scrutinized Environment. Research contribution is in introducing a supported process concerning the effective efficient management of privacy requirements occurring in organizations. PRIMROSE was the outcome of deductive reasoning subjected to a focus group and eight DPO interviewees scrutiny. Practical contribution is in setting the missing link regarding a generally recognized privacy management method to guide practitioners in which the elements originate from the qualitative research supporting root definitions semantics, considering, among others, principles, stages, processes, enablers and composite requirements.